A novel physical layer security approach in OFDMA‐MISO networks in the presence of noncooperative and cooperative adversary users with unknown mode. Issue 6 (16th May 2018) - Taghipour, Javad; Azmi, Paeiz; Mokari, Nader
Abstract: This paper proposes a novel physical layer security approach in an orthogonal frequency division multiple access system. Then, a joint subchannel assignment and power allocation method is proposed. It is assumed that there are multiadversary users in the considered orthogonal frequency division multiple access–based network. Each adversary user can be a passive user (ie, he/she just eavesdrops) or an active user (ie, he/she sends jamming to make disturbance). The adversary users can choose active or passive mode according to their situation in the network. In a real network, legitimate users do not have deterministic information about the passive and active modes of adversary users. Here, we assume that the active and passive modes of adversary users are unknown. We also introduce both noncooperative and cooperative scenarios for adversary users. In the noncooperative scenario, the adversary users do not have cooperation and they act independently. In the cooperative scenario, they have cooperation with each other to eavesdrop well and reduce the secrecy rate of the network. For the noncooperative adversary users, a probabilistic method is proposed to estimate the active or passive mode of the adversary users. Based on the proposed probabilistic method, the average secrecy rate for the network is obtained. For the cooperative adversary users, we assume that they are smart and organized; it means that they choose their active or passive mode based on the situation of other adversary users to reach the best performance. Since the total secrecy rate in two scenarios is nonconvex, the corresponding optimization problem is nonconvex. We propose an iterative method for joint subchannel assignment and power allocation to maximize the total secrecy rate of the network. A linear search method is proposed for the subchannel assignment, and a successive convex approximation approach is proposed to solve the power allocation problem. Abstract : This paper proposes a new physical layer security model for an OFDMA‐MISO network in the presence of cooperative and noncooperative adversary users. In the noncooperative scenario, the adversary users do not have cooperation and they act independently. In the cooperative scenario, they have cooperation with each other to eavesdrop well and reduce the secrecy rate of the network. We propose an iterative method for joint subchannel assignment and power allocation to maximize the total secrecy rate of the network.